‘It’s a generational thing, really’ : understandings of sexual rights in a digital age - Spisak Sanna (United Kingdom, 2025)
Deriving from a large-scale research project on intimacy in data-driven culture in Finland, I build on a sub-study examining Finland’s presumed sexual digital divide between generations. I analysed in-depth, semi-structured research discussions with six social media users who actively participated in the online discussion following the posting of a video on TikTok by the National Board of Investigation on the potential risks and dangers of sending nude images online. I wanted to know why this particular ‘awareness-raising video’ gained so much negative feedback from its young audiences on TikTok and other social media platforms. By using the idea of ‘generational sexualities’, I focus on the shared social imaginary the research participants seem to have on the sexual and digital divide between generations. As a result of my analysis, I propose that the idea of a generational gap regarding the digital modes of sexual engagement is a culturally and socially shared narrative contributing to a disconnective effect between the generations in sexual matters. Furthermore, the analysis of my research materials reveals that young people’s ‘full sexual rights’ operate as a specific generational narrative that organises and structures my research participants’ perspectives of what is inclusive and socially just sexual education. The educational efforts must go beyond risk and harm as ‘no-sexting’ educational materials may contribute to sexual discrimination and marginalisation, increase social inequality and negatively impact young people’s sexual wellbeing.